Gender ideology versus sex difference - aspect of the right to family. Outline of legal regulations - Świto, Lucjan (Studia Warmińskie, 2012)
The right to have family is one of the fundamental rights of man, which is determined and protected by many enactments of current legal systems. It’s however impossible not to see that social transformations of XX century and along with them new currents of thoughts more and more undermine the fundamental axioms regarding man and his sexual identity. Gender ideology, which opposes the “traditional” understanding of family is an expression of that. Gender Ideology rejects dichotomous division of the society in two sexes by introducing „a cultural sex” (social) which is not identical with the biological one. This article, based on an analysis of polish, european and canon law, is an attempt to answer the a question whether gender ideology has entered legal systems and whether with this regard we are to redefine the notion of family and marriage. Analysis of the above mentioned three legal systems leads us to conclusion that gender ideology is explicitly foreign to the canon law. In the current polish law there could be observed some symptoms of it whereas in the european law the gender ideology has been widely implemented. The gender mainstreaming is highly effective in this area. The new definition of family in european law has already become a fact and its assimilation into legal systems of respected member states (even as conservative as Poland), if such a promotion of gender ideology will be maintaind, is just a matter of time.